Analisis Faktor yang Memengaruhi Adopsi Aplikasi No Thanks dalam Mendukung Gerakan BDS terhadap Israel - Nurmuhsina, St.; Nuranisah, Nuranisah; Syamila, Maryam Hasnaa'; Ramadhan, Muhammad Sayyid; Nabarian, Tifanny (Jurnal Informatika Terpadu, 2025)
This study analyzes the factors influencing the adoption of the No Thanks application in Indonesia to support the BDS movement. The research aims to understand how technology aids social movements, particularly in advocating Palestinian rights. Using the Technology Acceptance Model (TAM), this study employs qualitative and quantitative methods, including hypothesis testing, statistical analysis, validity, and reliability tests. A survey was conducted on 108 respondents, primarily female (60.2%), aged 17-25 years (98.1%), students (92.6%), with monthly expenses ranging from Rp 100,000 to Rp 300,000 (40.7%), and mostly residing in West Java (69.4%). The findings reveal significant relationships among research variables. Social Awareness, Social Norms, Value Compatibility, Technology Self-Efficacy, Information Availability, and application features influence Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), which subsequently affect Attitude (A) and Behavioral Intention (BI). The study concludes that intuitive interface design, accessible information, and social relevance are key to enhancing adoption and strengthening the role of technology in social movements.